Software as a Service and Habeas Data: An Approach from Private and Constitutional Law in Colombia - Mendoza Munar, Lainiver (DIXI, 2018)
Theme and scope: This reflection paper aims to analyze personal data processing in Colombia bycompanies that offer software as a service (SaaS), especially the regulation regarding habeas datain Colombia and related principles established by case law. Characteristics: Various contractual types are analyzed from private law and the importance of regulat-ing personal data processing in the platforms providing the SaaS service is determined, based not onlyon constitutional principles, but also on the use of private law regulations. Findings: The application of constitutional principles plays a significant role when regulating the con-tractual types of technology companies, although contracts are also crucial according to the principleslaid down by the law and case law on personal data. Conclusions: We could demonstrate the importance of determining product ownership and data own-ership, as well as the relevance of stipulating these aspects in the technological platforms using theSaaS model to operate in Colombia.
Keywords: cloud computing; personal data; constitutional law; property law; private law; social media; software as a service